THE IMPACT OF STRATEGIC GOVERNANCE AND RESEARCH CAPACITY ON HIGHER EDUCATION COMPETITIVENESS: EVIDENCE FROM UZBEKISTAN USING AN ARDL APPROACH (Marketing Journal, 2026)
AbstractThis study examines the long-run and short-run effects of strategic governancequality and research capacity on the competitiveness of higher education in Uzbekistan.Using annual time-series data for the period 2000-2022, higher educationcompetitiveness is proxied by tertiary school enrollment, while institutional quality andscientific capacity are captured by government effectiveness, regulatory quality,scientific and technical journal articles, and the number of researchers in R&D. Giventhe mixed order of integration and small sample size, the Autoregressive DistributedLag (ARDL) bounds testing approach is employed to investigate cointegration anddynamic relationships among the variables. The results provide evidence of a stablelong-run equilibrium relationship between higher education enrollment, governancequality, and research capacity. Scientific publication output and the stock of R&Dresearchers are found to be key long-run drivers of tertiary education expansion, whileinstitutional quality indicators influence higher education development throughdelayed and dynamic adjustment processes. The error-correction term confirms asignificant speed of adjustment toward long-run equilibrium, indicating that deviationsfrom the steady-state path are corrected over time. These findings highlight the crucialrole of strategic governance reforms and sustained investment in research andinnovation infrastructure in building sustainable competitive advantage in the highereducation sector of transition economies.Keywords: higher education competitiveness, governance quality, researchcapacity, ARDL model, cointegration, institutional quality, R&D, Uzbekistan.